The Effect of Liraglutide on Weight Loss in Women with Polycystic Ovary Syndrome: An Observational Study - Rasmussen, Christina B.; Lindenberg, Svend (Frontiers in Endocrinology, 2014)
Abstract Objective: The aim of the present study was to evaluate the effect of the glucagon-like peptide-1 analogue liraglutide on weight loss in overweight and obese women with polycystic ovary syndrome. Methods: In an observational study, 84 overweight or obese women with polycystic ovary syndrome were treated with liraglutide. Baseline characteristics and weight changes at clinical follow-up were recorded. Main outcome measures were absolute and relative weight loss. Results: In overweight or obese women with polycystic ovary syndrome treated with liraglutide for a minimum of 4 weeks a mean weight loss of 9.0 kg (95% CI: 7.8-10.13, p<0.0001) and a mean decrease in BMI of 3.2 kg/m2 (95% CI: 2.8-3.6, p<0.0001) was found. A weight loss of more than 5% and 10% of baseline weight was seen in 81.7% and 32.9% of patients, respectively. The mean duration of treatment with liraglutide was 27.8 weeks (SD 19.2). Conclusion: Treatment with liraglutide in combination with metformin and lifestyle intervention resulted in a significant weight loss in overweight and obese women with polycystic ovary syndrome, indicating that liraglutide may be an effective alternative for weight loss in this group of patients. However, larger placebo-controlled studies are needed to confirm this.